Dual‐Mode Superresolution Imaging Using Charge Transfer Dynamics in Semiconducting Polymer Dots. Issue 37 (15th July 2020) - Jiang, Yifei; Hu, Qiongzheng; Chen, Haobin; Zhang, Jicheng; Chiu, Daniel T.; McNeill, Jason
Abstract: In a conjugated polymer‐based single‐particle heterojunction, stochastic fluctuations of the photogenerated hole population lead to spontaneous fluorescence switching. We found that 405 nm irradiation can induce charge recombination and activate the single‐particle emission. Based on these phenomena, we developed a novel class of semiconducting polymer dots that can operate in two superresolution imaging modes. The spontaneous switching mode offers efficient imaging of large areas, with <10 nm localization precision, while the photoactivation/deactivation mode offers slower imaging, with further improved localization precision (ca. 1 nm), showing advantages in resolving small structures that require high spatial resolution. Superresolution imaging of microtubules and clathrin‐coated pits was demonstrated, under both modes. The excellent localization precision and versatile imaging options provided by these nanoparticles offer clear advantages for imaging of various biological systems. Abstract : Pdots and moonbeams : By controlling the population of photogenerated holes, dual‐mode superresolution imaging with semiconducting polymer dots was demonstrated. The localization precision achieved is 3–8 times better than the typical resolution obtained by localization of dyes and fluorescent proteins, which allows the hollow structure of microtubules to be resolved.